Four new rare-earth nitronyl nitroxide radical complexes: Magnetic and luminescent properties. (1st April 2018) - Yang, Shuai-Liang; Wang, Rui-Rui; Jin, Xiao-Jiao; Zhang, Chen-Xi; Wang, Qing-Lun
Graphical abstract: In complexes1 –4, isolated mononuclear molecules connect each other through intermolecular hydrogen bonds to form 3D supermolecular framework. Quantitative estimate of the magnetic interaction parameters between paramagnetic species in complexes1 –4, the fitting results show that there are ferromagnetic interactions between Gd(III) ions and radicals in complex1 . The luminescence properties of complex2 exhibit that it may potentially be acted as luminescence-based sensor for quantitative and highly sensitive detection of Cr2 O7 2− ion due to nearly linear at low concentration and the low detection limit (0.01 μM). Abstract: Four new rare-earth nitronyl nitroxide radical complexes, [Ln(hfac)3 (NITPh-Pa)2 ][0.5CH3 (CH2 )5 CH3 ] (Ln = Gd(1 ), Tb(2 ), Dy(3 ), Ho(4 ), hfac = hexafluoroacetylacetonate, NITPh-Pa = 2-(3′, 4′-dioxylmethylene-phenyl)-4, 4, 5, 5-tetramethyl-imidazoline-1-oxyl-3-oxide), have been synthesized. The X-ray crystal structure analysis revealed that four compounds have similar mononuclear tri-spin structures, in which the Ln(III) ions are eight-coordinated by two nitronyl nitroxide radicals and three hexafluoroacetylacetonate ligands to form a slightly distorted dodecahedron. In complexes1 –4, isolated mononuclear molecules connect each other through intermolecular hydrogen bonds to form 3D supermolecular framework. Magnetic investigation indicates there are ferromagnetic interactions between Gd(III) ions and radicals in complex1 . Alternating current(ac) magnetic susceptibilities of complexes2 and3 show that there are no non-zero out-of-phase signal, which indicates the inexistence of slow magnetic relaxation. The luminescence properties of complex2 exhibit the characteristic emission peaks of Tb 3+ ions and the potential for recognition of Cr2 O7 2− and Cr 3+ ions. Furthermore, nearly linear at low concentration and the low detection limit (0.01 μM) indicate that complex2 may potentially be acted as luminescence-based sensor for quantitative and highly sensitive detection of Cr2 O7 2− ion.